A Plot‐Scale Monitoring Experiment To Assess The Agricultural Non‐Point Source Pollution Reductions Achieved By Silt Fences and Berms†. (8th July 2016) - Jang, Min Won; Kim, Dong Hyeon; Jang, Jeong Ryeol; Kim, Sang Min
Abstract: The objective of this study was to assess the non‐point source pollution reductions by a silt fence and berm through field monitoring. Experimental plots were established in two sizes on three slopes (110 m 2 on 3 and 9% slopes, and 225 m 2 on 6% slope). Flumes were used to monitor plot runoff. Runoff samples were collected during heavy rainfall (12 events from 2011 to 2014) for subsequent analysis. Cultivated crops were radish, Chinese cabbage and soybean. Runoff from the silt fence and berm treatment plots was 23.1 and 25.8% lower, respectively, than that from the control plot. On average the silt fence reduced BOD losses by −10.0% (i.e. 10% increase), COD by 28.7%, T‐N by 42.5%, T–P by 22.7%, and SS by 48.0% compared to losses from the control plot. The berm reduced BOD losses by 34.1%, COD by 30.0%, T‐N by 30.8%, T–P by 68.9%, and SS by 59.9% compared to losses from the control plot. The SS load reductions were statistically significant (5% level). Thus, the silt fence and berm were both effective in reducing pollutant losses in surface runoff. However, long‐term monitoring is required to obtain a more quantitative and reliable description of the reduction effect for diverse crops. Copyright © 2016 John Wiley & Sons, Ltd.